2013
DOI: 10.1111/hiv.12035
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of digital anal cancer screening examinations in HIV‐positive homosexual men

Abstract: ObjectivesAnal cancer is more common in HIV-positive homosexual men than in HIV-negative homosexual men and the general population. Earlier diagnosis leads to improved prognosis. We aimed to determine if regular anal inspection and digital examination of asymptomatic homosexual men attending for routine HIV care were acceptable and to record the rate of referral for diagnosis of potentially malignant anal lesions. MethodsWe offered anal examinations to consecutive homosexual men with HIV infection aged Ն 35 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“… reported high HRA acceptance, with or without biopsy, among a cohort that included 3% women but did not report results for women separately and did not distinguish patients having a first‐time HRA. Other studies of anal examinations for cancer screening have reported similarly high tolerability and willingness of patients to comply with screening, including studies of anal Pap smears , self‐collected anal swabs and annual anorectal digital examinations to detect anal cancer in HIV‐infected MSM .…”
Section: Discussionmentioning
confidence: 99%
“… reported high HRA acceptance, with or without biopsy, among a cohort that included 3% women but did not report results for women separately and did not distinguish patients having a first‐time HRA. Other studies of anal examinations for cancer screening have reported similarly high tolerability and willingness of patients to comply with screening, including studies of anal Pap smears , self‐collected anal swabs and annual anorectal digital examinations to detect anal cancer in HIV‐infected MSM .…”
Section: Discussionmentioning
confidence: 99%
“…Only one small, short term study on acceptability has been published (315). In this study 28% of those approached declined to take part.…”
Section: Anal Dysplasiamentioning
confidence: 98%
“…Hence, high-risk HPV and especially HPV16 detection on anal swabs could be used to identify patients at high risk of anal cancer, which could trigger regular monitoring and procedures such as high-resolution anoscopy and biopsy [11,12]. Nevertheless, anal examinations performed by clinicians can raise intimacy problems, and they are not accepted by many patients, for instance by 28% of the 142 HIV-positive MSM who were offered proctologic examination in a recent study [13]. Thus, many HIV-infected patients are not screened for anal cancer although they are at-risk individuals [2,5].…”
Section: Introductionmentioning
confidence: 99%